Switch to fulvestrant and palbociclib versus no switch in advanced breast cancer with rising ESR1 mutation during aromatase inhibitor and palbociclib therapy (PADA-1): a randomised, open-label, multicentre, phase 3 trial. Issue 11 (November 2022) - Bidard, François-Clément; Hardy-Bessard, Anne-Claire; Dalenc, Florence; Bachelot, Thomas; Pierga, Jean-Yves; de la Motte Rouge, Thibault; Sabatier, Renaud; Dubot, Coraline; Frenel, Jean-Sébastien; Ferrero, Jean Marc; Ladoire, Sylvain; Levy, Christelle; et al.
Summary: Background: In advanced oestrogen receptor-positive, HER2-negative breast cancer, acquired resistance to aromatase inhibitors frequently stems from ESR1 -mutated subclones, which might be sensitive to fulvestrant. The PADA-1 trial aimed to show the efficacy of an early change in therapy on the basis of a rising ESR1 mutation in blood (b ESR1 mut ), while assessing the global safety of combination fulvestrant and palbociclib. Methods: We did a randomised, open-label, phase 3 trial in 83 hospitals in France. Women aged at least 18 years with oestrogen receptor-positive, HER2-negative advanced breast cancer and an Eastern Cooperative Oncology Group performance status of 0–2 were recruited and monitored for rising b ESR1 mut during first-line aromatase inhibitor (2·5 mg letrozole, 1 mg anastrozole, or 25 mg exemestane, orally once per day, taken continuously) and palbociclib (125 mg orally once per day on days 1–21 of a 28-day cycle) therapy. Patients with newly present or increased b ESR1 mut in circulating tumour DNA and no synchronous disease progression were randomly assigned (1:1) to continue with the same therapy or to switch to fulvestrant (500 mg intramuscularly on day 1 of each 28-day cycle and on day 15 of cycle 1) and palbociclib (dosing unchanged). The randomisation sequence was generated within an interactive web response system using a minimisation method (with an 80% random factor); patients were stratified according to visceral involvement (present or absent) and the time from inclusion to b ESR1 mut detection (<12 months or ≥12 months). The co-primary endpoints were investigator-assessed progression-free survival from random assignment, analysed in the intention-to-treat population (ie, all randomly assigned patients), and grade 3 or worse haematological adverse events in all patients. The trial is registered with Clinicaltrials.gov (NCT03079011 ), and is now complete. Findings: From March 22, 2017, to Jan 31, 2019, 1017 patients were included, of whom 279 (27%) developed a rising b ESR1 mut and 172 (17%) were randomly assigned to treatment: 88 to switching to fulvestrant and palbociclib and 84 patients to continuing aromatase inhibitor and palbociclib. At database lock on July 31, 2021, randomly assigned patients had a median follow-up of 35·3 months (IQR 29·2–41·4) from inclusion and 26·0 months (13·8–34·3) from random assignment. Median progression-free survival from random assignment was 11·9 months (95% CI 9·1–13·6) in the fulvestrant and palbociclib group versus 5·7 months (3·9–7·5) in the aromatase inhibitor and palbociclib group (stratified HR 0·61, 0·43–0·86; p=0·0040). The most frequent grade 3 or worse haematological adverse events were neutropenia (715 [70·3%] of 1017 patients), lymphopenia (66 [6·5%]), and thrombocytopenia (20 [2·0%]). The most common grade 3 or worse adverse events in step 2 were neutropenia (35 [41·7%] of 84 patients in the aromatase inhibitor and palbociclib group vs 39 [44·3%] of 88 patients in the fulvestrant and palbociclib group) and lymphopenia (three [3·6%] vs four [4·5%]). 31 (3·1%) patients had grade 3 or worse serious adverse events related to treatment in the overall population. Three (1·7%) of 172 patients randomly assigned had one serious adverse event in step 2: one (1·2%) grade 4 neutropenia and one (1·2%) grade 3 fatigue among 84 patients in the aromatase inhibitor and palbociclib group, and one (1·1%) grade 4 neutropenia among 88 patients in the fulvestrant and palbociclib group. One death by pulmonary embolism in step 1 was declared as being treatment related. Interpretation: PADA-1 is the first prospective randomised trial showing that the early therapeutic targeting of b ESR1 mut results in significant clinical benefit. Additionally, the original design explored in PADA-1 might help with tackling acquired resistance with new drugs in future trials. Funding: Pfizer.